2018
DOI: 10.1016/s1474-4422(18)30242-4
|View full text |Cite|
|
Sign up to set email alerts
|

Imaging features and safety and efficacy of endovascular stroke treatment: a meta-analysis of individual patient-level data

Abstract: Medtronic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
272
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 315 publications
(298 citation statements)
references
References 29 publications
21
272
4
1
Order By: Relevance
“…We previously reported that EVT may result in better functional independence in these patients with decreasing likelihood of benefit as stroke size increases and time progresses. In a recent HERMES (Highly Effective Reperfusion evaluated in Multiple Endovascular Stroke Trials) meta‐analysis assessing functional and safety outcomes based on baseline CT and MRI assessment, a significant improvement in functional outcomes was shown in patients with ASPECTS 3 to 5; however, an increase in symptomatic ICH was also found . Another HERMES meta‐analysis demonstrated improvement in outcomes with thrombectomy in patients with an ischemic core volume > 70ml .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that EVT may result in better functional independence in these patients with decreasing likelihood of benefit as stroke size increases and time progresses. In a recent HERMES (Highly Effective Reperfusion evaluated in Multiple Endovascular Stroke Trials) meta‐analysis assessing functional and safety outcomes based on baseline CT and MRI assessment, a significant improvement in functional outcomes was shown in patients with ASPECTS 3 to 5; however, an increase in symptomatic ICH was also found . Another HERMES meta‐analysis demonstrated improvement in outcomes with thrombectomy in patients with an ischemic core volume > 70ml .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent HER-MES (Highly Effective Reperfusion evaluated in Multiple Endovascular Stroke Trials) meta-analysis assessing functional and safety outcomes based on baseline CT and MRI assessment, a significant improvement in functional outcomes was shown in patients with ASPECTS 3 to 5; however, an increase in symptomatic ICH was also found. 25 Another HERMES meta-analysis demonstrated improvement in outcomes with thrombectomy in patients with an ischemic core volume > 70ml. 26 However, there were imbalances in baseline characteristics that could not be adjusted for due to the limited sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The latest HERMES collaboration analysis based on individual patient data from RCTs (MR CLEAN, ESCAPE, EXTEND-IA, SWIFT PRIME, REVASCAT, THRACE, and PISTE) showed that thrombectomy led to better clinical outcomes at 90 days across a broad range of imaging categories, including ASPECTS <6 (OR=1.58 for ASPECTS 5–7 and OR=2.15 for ASPECTS 0–4) and infarcts affecting >1/3 of MCA territory (OR 1.7), supporting the value of thrombectomy in some patients with large infarcts at baseline 28. However, thrombectomy in patients with such unfavorable imaging profiles had higher rates of symptomatic intracranial hemorrhage than in the control group.…”
Section: Indications For Thrombectomymentioning
confidence: 80%
“…Of 485 enrolled patients in the overall BEST study, 177 underwent CTP and were included in the analyses. The median age was 69 years (interquartile range [IQR]: 57-81), 87 were female (49%), with a median baseline NIHSS of 17 (IQR: [11][12][13][14][15][16][17][18][19][20]. Seventy-two patients (41%) presented in the early window.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, according to data from the HERMES collaboration, the benefit of thrombectomy persisted among patients whose ASPECTS score was 6‐8 (cOR: 2.34, 95% CI: 1.68‐3.26 for a shift in 90‐day mRS) but was absent if the baseline ASPECTS was 0‐5 (cOR: 1.24, 95% CI: .62‐2.49) . In a subsequent meta‐analysis, including two additional randomized clinical trials, the benefit of early window thrombectomy over medical therapy persisted despite ASPECTS of 0‐4 (cOR: 2.15, 95% CI: 1.06‐4.37) . While these patients also experienced higher rates of sICH with intervention (OR: 5.00, 95% CI: 1.30‐19.25), there was no significant increase in mortality (OR: .81, 95% CI: .36‐1.81).…”
Section: Discussionmentioning
confidence: 99%